Cone beam computed tomography in detecting the second mesiobuccal canal in the upper molars: A pilot study - Othman, Noor Ilyani (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Root canal treatment aims to heal and/or prevent apical periodontitis. It is accomplished by removing inflamed or necrotic pulp, followed by sealing with the appropriate materials. Studies show that the endodontic treatment of the maxillary molars has the highest failure rate because of anatomical variations in the mesiobuccal (MB) roots. Purpose: This study aims to evaluate cone beam computed tomography (CBCT) to accurately identify the second mesiobuccal (MBII) canal in human maxillary first molars. Methods: The investigation was approved by the Research Ethics Committee of the Research Management Institute, Universiti Teknologi MARA (UiTM). Images were sourced from the Radiology Unit of the Centre for Oral Radiology Studies, Faculty of Dentistry, UiTM. CBCT images of permanent maxillary molars (n = 24) were selected. The images were of intact permanent maxillary first molars with complete root formation, with or without the presence of obturation material. The presence or absence of the MBII canals was analyzed by three examiners, and the data were recorded. Results: The MBII canals were present in 86% (n = 19) of the investigated upper first molars. All of the previously endodontically treated teeth (n = 10) revealed the presence of MBII canals, which were not obturated. Seventy-five percent (n = 3) of the patients exhibited four canals in both the right and left upper first molars. Conclusion: The MB roots of maxillary molar teeth have more variations in their canal system than the other two roots. CBCT is a good diagnostic tool for detecting and mapping the MB root-canal system and can potentially improve the quality of endodontic treatment.